SYNTHESIS OF PLANT-MEDIATED SILVER NANOPARTICLES USING LYCOPERSICON ESCULENTUM L. EXTRACT AND EVALUATION OF THEIR ANTIMICROBIAL ACTIVITIES - SMARANIKA DAS; UMESH KUMAR PARIDA; BIRENDRA KUMAR BINDHANI (International Journal of Pharma and Bio Sciences, 2014)
Present investigation deals with the synthesis of silver nanoparticles (AgNPs) from Lycopersicon esculentum L. through simple and eco-friendly chemical methods. In this technique, silver nitrate has been used as the metal precursor and hydrazine hydrate as a reducing agent. The nanoparticles thus obtained from Lycopersicon esculentum L. have been analysed and characterised by Scanning Electron Microscopy (SEM) and Energy-Dispersive Spectroscopy (EDX). The average diameter of the AgNPs, whose morphology has been determined by SEM, was found to be 70 - 90nm. The EDX analysis was carried out with a range of 2–4 keV which confirmed that the nanoparticles dispersion in the presence of elemental silver with no other detectable impurity peaks. The silver nanoparticles were characterized which have bright prospects for application in different medical and industrial fields. The results showed that the silver nanoparticles, which are susceptible to different for each and every microorganism. The antimicrobial activity of silver nanoparticles (AgNPs) has been evaluated with Escherichia coli, gram negative bacteria. Importantly, though the kinetics of killing were altered, AgNPs retained potent bactericidal activity against E. coli at low pH. A molar-to-molar comparison was carried out to know the efficacy of AgNPs as compared to metronidazole (MTZ), amoxicillin (AMX) and clarithromycin (CLR).